Microlenses: Electrically Tunable Printed Bifocal Liquid Crystal Microlens Arrays (Adv. Mater. Interfaces 16/2020). Issue 16 (20th August 2020) - Kamal, Waqas; Lin, Jia‐De; Elston, Steve J.; Ali, Taimoor; Castrejón‐Pita, Alfonso A.; Morris, Stephen M.
Abstract : The cover picture, referring to the article number 2000578 by Waqas Kamal, Alfonso A. Castrejón‐Pita, Stephen M. Morris, and co‐workers, illustrates the possible application of printed bifocal liquid crystal microlens arrays in Augmented reality (AR) glasses. The bespoke microlenses are manufactured using a drop‐on‐demand printing process on surfactant treated glass substrates with in‐plane electrodes.